Analisis Isi Lambung Ikan Selais Terang Bulan (Kryptopterus bicirrhis, Valenciennes 1840) di Desa Rantau Kasih Sungai Kampar Kiri Propinsi Riau: Study on Gut content of Selais Terang Bulan fish (Kryptopterus bicirrhis, Valenciennes 1840) in Rantau Kasih village Kampar Kiri river, Riau Province - Ermi YENI; Roza ELVYRA (Universitas Jambi, 2017)
The study on gut content of Selais Terang Bulan fish (Kryptopterus bicirrhis) in Rantau Kasih village Kampar Kiri river was conducted from Februari-April 2017. The purpose of this study was to know about gut content of Selais Terang Bulan fish which was categorized as main food, supplementary food and additional food. The analysis is done based on the instruction of Natardjan and Jhingran (1961). The gut content was analized using the Index of preponderance. The result revealed that the main food of Selais Terang Bulan fish in Rantau Kasih village is adult Arthropoda with IP value (78.85%), and supplementary food is caterpillar (25.15%). Male and female fishes at have main food of adult Arthropoda with different percentages are (82.81%) male and female (71.32%). Based on the gut content analysis of Selais Terang Bulan fish was a carnivorous fish. Keyword: gut content analysis, Kryptopterus bicirrhis, Kampar kiri river